Transmedicalism, corporalities and society (Research, Society and Development, 2021)
The term transgender refers to those that do not identify with the gender given to them by society. Currently, gender studies have shown that there are many ways of experiencing transsexuality, since it is an identity characteristic. Nevertheless, transmedicalism is the perspective that considers only one manner of experiencing transsexuality. Starting from this notion, the objective of this paper is to discuss some contemporary manifestations of transmedicalism, with emphasis on Brazilian society, as well as the negative repercussions of this belief for trans subjects. Therefore, uses bibliographic research as a method and recurs to queer theorist to base its understanding of gender and trans identities. This research begins by explaining the origin of the belief in the true transsexual and demonstrating how it still influences the health care of trans people in Brazil. Then explains the concept of transmedicalism and discuss it presence on health protocols and in the narratives of some trans people. Finally, presents queer presupposes and uses then to problematize transmedicalism.